(untitled) (Politeja, 2025)
„DIPLOMACY OF EQUILIBRE”: BETWEEN HISTORICAL HERITAGE AND GEOPOLITICAL RIVALRY. EMMANUEL MACRON’S POLICY TOWARDS THE MIDDLE EAST France has particularly strong historical ties with the Middle East region placed at the crossroads of three continents. Here, it has for decades acted as a mediator between Israel, the Palestinians and the Arab states, maintaining as wide a range of influence and strategic interests as possible. ‘The Arab policy’ of de Gaulle emphasised French exceptionalism, rank (‘la grandeur’) and an independent role as a ‘power of balance’, which provided an alternative to non-engaged countries in particular through almost unconditional arms supplies. The article aims at deeply analysing the evolution and contemporary objectives of French Arab policy and attempts to answer the question: does France still play the role of an independent and balanced political power capable of achieving lasting stability in this part of the world? Does Emmanuel Macron’s Middle East policy represent a continuation of the traditional ‘Arab policy’ course in the face of the new threats determining France’s interests in the Middle East region?